Compassion and Loving-Kindness Meditation: An Overview and Prospects for the Application in Clinical Samples. Issue 4 (July 2018) - Graser, Johannes; Stangier, Ulrich
Abstract : Objectives: This article presents a brief overview of the empirical evidence of well-established mindfulness interventions and an in-depth review of less-established compassion-based interventions (CBIs) and loving-kindness meditation (LKM). Definitions, cognitive and physiological mechanisms, and methods of assessment are discussed. Method: A literature review using the databases Google Scholar, PsycINFO, and PubMed was conducted. Results: Whereas the efficacy of mindfulness-based stress reduction and mindfulness-based cognitive therapy has been documented in many trials, only seven randomized, controlled trials have been completed on CBIs and LKM. In these trials, CBIs were effective in treating psychotic disorders, affective disorders with psychotic features, major depressive disorder, eating disorders, and patients with suicide attempts in the past year; LKM was effective in treating chronic pain; and a combination of both was effective for borderline personality disorder. A larger number of nonrandomized studies indicate that CBIs and LKM may be effective in treating a wide range of clinical conditions, including depression, anxiety disorders, chronic pain, and posttraumatic stress disorder. Conclusions: Further studies are needed to confirm the promising effects of CBIs and LKM. Preliminary evidence suggests that both approaches might be beneficial across various clinical populations. Future studies need to clarify whether these approaches might be options as stand-alone treatments or as adjuncts or augmentation of evidence-based methods in psychotherapy.